2014
DOI: 10.1021/ic500971z
|View full text |Cite
|
Sign up to set email alerts
|

Enlarging the π System of Phosphorescent (C^C*) Cyclometalated Platinum(II) NHC Complexes

Abstract: Cyclometalated (C^C*) platinum(II) N-heterocyclic carbene (NHC) complexes are emerging as a new class of phosphorescent emitters for the application in organic light-emitting devices (OLEDs). We present the synthesis of six new complexes of this class to investigate the influence of extended π systems. Therefore, six different NHC ligands with a varying number of additional phenyl substituents were used in combination with the monoanionic acetylacetonate (acac) ligand to obtain complexes of the general formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
101
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 65 publications
8
101
0
Order By: Relevance
“…Replacing the acac ligand with a more bulky congener, namely, the dimesitoylmethanato (mesacac) ligand, led to increased solubility, reduced aggregation behavior, and an improvement of the photoluminescence properties to 91 %, 466 nm, and 18.9 μs (Scheme ) 7c. Furthermore, we recently showed that an extension of the π‐system in the rigid NHC backbone could increase the quantum yield 7e. In the present study we combine these earlier results in one system and investigate the influence of different ways of attaching the DBF fragment to the heterocyclic system and thus the metal center with the goal to reduce the decay lifetime, which remains a very critical aspect in overall device stability.…”
Section: Methodsmentioning
confidence: 99%
“…Replacing the acac ligand with a more bulky congener, namely, the dimesitoylmethanato (mesacac) ligand, led to increased solubility, reduced aggregation behavior, and an improvement of the photoluminescence properties to 91 %, 466 nm, and 18.9 μs (Scheme ) 7c. Furthermore, we recently showed that an extension of the π‐system in the rigid NHC backbone could increase the quantum yield 7e. In the present study we combine these earlier results in one system and investigate the influence of different ways of attaching the DBF fragment to the heterocyclic system and thus the metal center with the goal to reduce the decay lifetime, which remains a very critical aspect in overall device stability.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the electronic properties of both the cyclometalated and the carbene fragments can be fine‐tuned. For example, modifying the π‐conjugation on the C^C* ligand, the phosphorescent decay time can be changed between 8 and 400 μs . Recently we also reported that the introduction of a heteroatom in the backbone of the N ‐heterocyclic carbene changes the photophysical properties of the C^C* platinum(II) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the carbene complex was verified by the disappearance of the characteristic NCHN protons ignal of the imidazolium salt in the 1 HNMR experiment and the appearance of the characteristic ipso carbon signal of the carbene at 163-164 ppm in the 13 CNMR experiment. Thermal stability of all complexes was analyzed by determining their melting point, which are in the range of 234 8C (11)t om ore than 350 8C (12). Thermal stability of all complexes was analyzed by determining their melting point, which are in the range of 234 8C (11)t om ore than 350 8C (12).…”
mentioning
confidence: 99%
“…This assignment is confirmed by concentration dependent measurements at 77 Ki naglassy 2Me-THF matrix (Figure S7). [10c] Strikingly,t his phenomenon is not observed in the case of the analogous benzimidazole platinum(II) complex [12] (Figure S13 and Table S3). However,t he emission at lower energies maintains an unstructured profile.…”
mentioning
confidence: 99%
See 1 more Smart Citation